2017
DOI: 10.1016/j.ophtha.2017.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Benign Yellow Dot Maculopathy

Abstract: Objective To describe a novel macular phenotype that is associated with normal visual function. Design Retrospective observational case series. Participants 36 affected individuals from 23 unrelated families. Methods This was a retrospective study of patients who had a characteristic macular phenotype. Subjects underwent a full ocular examination, electrophysiological studies, spectral domain optical coherence tomography (OCT) and fundus autofluorescence imaging. Genomic analyses were performed using hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…This is the first report of yellow dot maculopathy following the original study in which it was described. 3 The families included in that study were mostly white, and none was reported to be of North African descent, as the family we report here. This may indicate that the prevalence of this phenotype is more common, and its relatively benign nature may be responsible for its previous lack of recognition and under-reporting.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…This is the first report of yellow dot maculopathy following the original study in which it was described. 3 The families included in that study were mostly white, and none was reported to be of North African descent, as the family we report here. This may indicate that the prevalence of this phenotype is more common, and its relatively benign nature may be responsible for its previous lack of recognition and under-reporting.…”
Section: Discussionmentioning
confidence: 70%
“…He was a young patient, with bilateral macular yellow dots compatible with those described in the original study. 3 His VA and color vision were unaffected, there was no progression over 6 years of follow up, and he had no abnormalities in OCT and electrophysiologic testing. Similar findings were discovered in his mother's eyes, but not his father, consistent with autosomal dominant inheritance.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Recently, a novel macular phenotype termed ‘benign yellow dot maculopathy’ has been described by Dev Borman et al 2 To date, reports of this phenotype describe non-progressive bilateral macular yellow dots with normal visual acuity and color vision. Herein, we present the first known case of unilateral benign yellow dot maculopathy.…”
Section: Introductionmentioning
confidence: 99%